FORMULATION DEVELOPMENT AND OPTIMIZATION OF EMPAGLIFLOZIN FILM COATED TABLET USING QUALITY-BY-DESIGN APPROACH - LAKAMBARE, SHRADDHA; ATUL PHATAK; MAHESH BHADAGALE; VARDHAMAN BAFNA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Development of robust and effective oral solid immediate release film coated tablet of empagliflozin using Quality-by-Design (QbD) approach was the objective of present research work. This belongs to Sodium Glucose Co-Transporter-2 inhibitors-oral hypoglycemic class to treat Type-2 diabetes mellitus and associated cardiovascular comorbidities. Methods: Assessment of risk factors (using Ishikawa fishbone diagram) was done by in-depth understanding of quality target product profile and critical quality attributes (CQAs) associated with material and process with justification. Randomized regular two levels full factorial design in addition with 5-center points was employed as Design of Experiment (DoE) tool. In this design, independent factors were concentrations of hydroxyl propyl cellulose (HPC SL) and croscarmellose sodium in mg. The responses selected for study were % drug release at 15-min in vitro dissolution time, disintegration time in sec, and hardness in Newton. Results: ANOVA and lack-of-fit demonstrated that stipulated independent variables have significant impact on response variables and best correlation was seen in actual and predicted value. This optimization method confirmed that HPC SL (8 mg) and croscarmellose sodium (4 mg) were ideal concentrations of binder and disintegrant, respectively, to prepare said formulation with desired quality attributes and it was found to be better with respect to stability and effectiveness against marketed reference formulation. Conclusion: QbD tools such as QTPP, CQAs, risk assessment, and DoE can be used in combination to optimize, screen, and understand the function of material and process parameters on quality characteristics of film-coated tablet.